2015 2nd International Conference on Information Science and Control Engineering 2015
DOI: 10.1109/icisce.2015.177
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Location Position Based on Bluetooth Signal Strength

Abstract: nowadays many systems with diverse technologies such as (GPS, Wi-Fi, Bluetooth, ZigBee, Ultra Wide Band, Ultrasounds, Infrared, etc...) can be used for indoor location. One of the biggest challenges in indoor location systems is to determine the actual indoor position of the user using a smart device (Phone, PC, etc...), due to their instability, cost, high-power consumption, low accuracy and low precision. To overcome those problems, we have designed, implemented and emulated an indoor location system based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(86 citation statements)
references
References 5 publications
1
82
0
3
Order By: Relevance
“…However, the studies of Feldmann, Kyamakya, Zapater, and Lue (2003), Bekkelien (2012), Rida et al (2015) and Kriz et al (2016) showed that position computation also occurs in the mobile device, thus improving user privacy. In this case, the Bluetooth sensors communicate with the server that stores the position information of the sensors, but the server does not compute position.…”
Section: Bluetooth-based Positioning Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the studies of Feldmann, Kyamakya, Zapater, and Lue (2003), Bekkelien (2012), Rida et al (2015) and Kriz et al (2016) showed that position computation also occurs in the mobile device, thus improving user privacy. In this case, the Bluetooth sensors communicate with the server that stores the position information of the sensors, but the server does not compute position.…”
Section: Bluetooth-based Positioning Systemmentioning
confidence: 99%
“…In this case, the Bluetooth sensors communicate with the server that stores the position information of the sensors, but the server does not compute position. The application in the mobile device requests the position information from the Bluetooth sensors before computing the position of the device with the information (Rida et al, 2015;Kriz et al, 2016;Bekkelien, 2012). In addition, the sensors are placed within the environment in such a way as to make their operation optimal.…”
Section: Bluetooth-based Positioning Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…It is used to connect wireless devices within a short distance, such as: Cellular phones, TV's, notebooks and stereos. For more detailed discussions on the application of this technology to the problem in question, see [17], [18], [19], [20] and [21].…”
Section: 23mentioning
confidence: 99%
“…Nowadays the LBS has several ways to deal with the Indoor Positioning Service(IPS), such as Bluetooth [2], IR (Infrared Radiation) [3], RF (Radiation Frequency) [3], ultrasound [4] and UWB (Ultra-Wide Bandwidth) [5]. Several of them rely on electromagnetic wave, nevertheless, the electromagnetic wave spreading can be influenced by multipath effect.…”
Section: Introductionmentioning
confidence: 99%